2015
DOI: 10.1200/jco.2015.33.3_suppl.666
|View full text |Cite
|
Sign up to set email alerts
|

Trial-level association between response-based endpoints (RBEs) and progression-free (PFS)/overall survival (OS) in first-line therapy for metastatic colorectal cancer (mCRC) in the ARCAD database.

Abstract: 666 Background: Early tumor shrinkage (ETS; ≥20% decrease from baseline) and early objective tumor response (EOTR; CR/PR by RECIST) are associated with improved PFS/OS to a similar extent than best overall response (BOR), confirmed response (ConfR) and non-progression rate (NPR; CR/PR/SD by RECIST) at the individual level in first-line mCRC (ASCO 2014, abstr 3538/3578). We assessed these RBEs at the trial level. Methods: Data were available on 12,185 pts enrolled in a total of 17 randomized trials of chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is in fact rare for individual level correlations between response and outcome to translate into trial level-surrogacy. In a study using the ARCAD database, Coart et al demonstrated that despite their prognostic importance at the individual level, the early response endpoints discussed above were not viable surrogates for PFS or OS at the trial level (36). The study also assessed the two conventional endpoints of best overall response and confirmed response.…”
Section: Response-based Endpointsmentioning
confidence: 99%
“…It is in fact rare for individual level correlations between response and outcome to translate into trial level-surrogacy. In a study using the ARCAD database, Coart et al demonstrated that despite their prognostic importance at the individual level, the early response endpoints discussed above were not viable surrogates for PFS or OS at the trial level (36). The study also assessed the two conventional endpoints of best overall response and confirmed response.…”
Section: Response-based Endpointsmentioning
confidence: 99%